ASUHAN KEPERAWATAN PADA KLIEN STROKE NON HEMORAGIK DENGAN MASALAH GANGGUAN MOBILITAS FISIK - Sulis Oktaviana, (2023)
Background : stroke is a disturbance of the nerves due to spontaneous blood circulation disturbances where symptoms such as disturbances in the brain stroke cause disability in patients who can survive such as the inability to care for themselves due to weakness in the extremities and reduced mobility which can interfere with daily life activities trigger factors Non hemorrhagic strokes are hypertension, high cholesterol, diabetes, smoking, being overweight and not exercising. Purpose : researchers are able to broaden their insights and benefits when providing care for Mr.D who has a non-hemorrhagic stroke. Results : Nursing problems are found in clients with the main diagnosis, namely impaired physical mobility related to neuromuscular disorders. Nursing interventions are range of motion exercises, namely by identifying limitations in joint movement, as well as monitoring the location of discomfort or pain when moving and recommend doing passive and active movement sequences systematically. Within 3x24 hours the problem of impaired physical mobility was partially resolved with the expected results, namely increased ROM range of motion, decreased limited movement, increased limb movement. Methods : this study used a qualitative research design, interviews, observations and physical examinations and documentation studies.